Git essentials : create, merge, and distribute code with Git, the most powerful and flexible versioning system available - Santacroce, Ferdinando (Packt Publishing, 2017)
Dive and explore into the latest addons of the latest Git. About This Book Master all the basic concepts of Git to protect your code and make it easier to evolve Use Git proficiently, and learn how to resolve day-by-day challenges easily This step-by-step guide is packed with examples to help you learn and work with Git's internals Who This Book Is For If you are a software developer with little or no experience of versioning systems, or you are familiar with other centralized versioning systems, then this book is for you. If you have experience in server and system management and need to broaden your use of Git from a DevOps perspective, this book contains everything you need. What You Will Learn Master Git fundamentals Be able to "visualize," even with the help of a valid GUI tool Write principal commands in a shell Figure out the right strategy to run change your daily work with few or no annoyances Explore the tools used to migrate to Git from the Subversion versioning system without losing your development history Plan new projects and repositories with ease, using online services, or local network resources In Detail Since its inception, Git has attracted skilled developers due to its robust, powerful, and reliable features. Its incredibly fast branching ability transformed a piece of code from a niche tool for Linux Kernel developers into a mainstream distributed versioning system. Like most powerful tools, Git can be hard to approach since it has a lot of commands, subcommands, and options that easily confuse newcomers. The 2nd edition of this very successful book will help you overcome this fear and become adept in all the basic tasks in Git. Building upon the success of the first book, we start with a brief step-by-step installation guide; after this, you'll delve into the essentials of Git. For those of you who have bought the first edition, this time we go into internals in far greater depth, talking less about theory and using much more practical examples. The book serves as a primer for topics to follow, such as branching and merging, creating and managing a GitHub personal repository, and fork and pull requests. You'll then learn the art of cherry-picking, taking only the commits you want, followed by Git blame. Finally, we'll see how to interoperate with a Subversion server, covering the concepts and commands needed to convert an SVN repository into a Git repository. To conclude, this is a collection of resources, links, and ap ...